A High‐Performance Membraneless Microfluidic Microbial Fuel Cell for Stable, Long‐Term Benchtop Operation Under Strong Flow. Issue 10 (25th February 2020) - Amirdehi, Mehran Abbaszadeh; Khodaparastasgarabad, Nastaran; Landari, Hamza; Zarabadi, Mir Pouyan; Miled, Amine; Greener, Jesse
Abstract: Strong control over experimental conditions in microfluidic channels provides a unique opportunity to study and optimize membraneless microbial fuel cells (MFCs), particularly with respect to the role of flow. However, improved performance and transferability of results to the wider MFC community require improvements to device stability under all applied operational conditions. To address these challenges, we present an easy‐to‐fabricate membraneless MFC that combines i) O2 protection via a gas diffusion barrier, ii) integrated graphite electrodes, and iii) optimized electrode placement to avoid cross‐contamination under all applied flow rates. Attention to all of these design features in the same platform resulted in the operation of a MFC with a pure‐culture anaerobic Geobacter sulfurreducens biofilm for half a year, that is, six times longer than previously reported, without the use of an oxygen scavenger. As a result of higher device stability under high flow rates, power densities were four times higher than reported previously for microfluidic MFCs with the same biofilm. Abstract : In full flow : The highest performing membraneless microfluidic microbial fuel cell (MFC) to date is presented. The device features a strictly anaerobic environment and robust graphite electrodes with optimized placement that avoids cross‐contamination between electrode compartments. The result is stable operation for six months for a pure Geobacter sulfurreducens biofilm, even under high flow rates. Beyond setting new benchmarks for power output and durability, results are expected to be more relevant to the wider MFC community.